2018
DOI: 10.1080/2162402x.2018.1541535
|View full text |Cite
|
Sign up to set email alerts
|

PD-L2 expression is correlated with the molecular and clinical features of glioma, and acts as an unfavorable prognostic factor

Abstract: Background: Gliomas are aggressive tumors with various molecular and clinical characteristics and exhibit strongly resistance to radio-chemotherapy. Programmed cell death 1 ligand 2 (PD-L2) is a cell surface protein, which was reported in many cancers, modulating cancer-associated immune responses, while the role of PD-L2 in gliomas remained unclear. Herein, we aimed to investigate the biological behaviors and clinical prognostic values of PD-L2 in gliomas.Methods: Totally, we enrolled RNA sequencing data of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 44 publications
3
35
1
Order By: Relevance
“…Similarly, PD-L2 expression across 1357 glioma samples conferred shorter survival times compared to low expressing counterparts. In addition, PD-L2 expression positively correlated with T-regulatory signatures indicating the functional role of PD-L2 in enhancing glioma immunosuppression(34). A similar study of 976 brain glioma samples showed the same functional implications of PD-L1 expression, whereby WHO grade IV gliomas had higher levels of PD-L1 expression compared to grade II and III gliomas.…”
mentioning
confidence: 70%
“…Similarly, PD-L2 expression across 1357 glioma samples conferred shorter survival times compared to low expressing counterparts. In addition, PD-L2 expression positively correlated with T-regulatory signatures indicating the functional role of PD-L2 in enhancing glioma immunosuppression(34). A similar study of 976 brain glioma samples showed the same functional implications of PD-L1 expression, whereby WHO grade IV gliomas had higher levels of PD-L1 expression compared to grade II and III gliomas.…”
mentioning
confidence: 70%
“…ing CGGA sequencing data, we calculated a transcriptional Notch pathway activation signature using GSVA. GSVA is a technique for characterizing activation of pathways from gene expression dataset 25 and is commonly used to identify expression enrichments between different samples/ group of samples [38][39][40][41] . In order to verify the credibility of the Notch score, correlation analysis was performed between our enrichment calculation and consensus Notch signaling genes.…”
Section: Results Establishment Of Notch Activation Signature In Clinimentioning
confidence: 99%
“…PD-1/PD-Ls axis is the most important immune checkpoints in cancer immunity, but whether PD-1/PD-Ls have notable influence on LGG biology is largely unknown. We have noticed two studies presented by Prof. Jiang's group reported that PD-L1 and PD-L2 were correlated with WHO grade system and poor prognosis in gliomas and GBM, as well as PD-L2 also had promising prognostic value in LGG [9,10]. In this research, we systematically evaluated PD-1/PD-Ls expression and their prognostic values in…”
Section: Discussionmentioning
confidence: 98%
“…Previously, PD-L1 and PD-L2 (PD-Ls) expression have been revealed to be correlated with poor prognosis of glioma [9,10]. As we all known, two main glioma subtypes,…”
Section: Introductionmentioning
confidence: 99%